A rare presentation of complication arising from Meckel's diverticulum in the form of diverticulotransverse colonic fistula in an adult. (3rd June 2015) - Lo, Tammy; Sagar, Jayesh; Trickett, Jonathan
Abstract : Meckel's diverticulum is a common congenital malformation of the gastrointestinal tract, reported to be present in 2–4% of the population. Although most patients with Meckel's diverticulum remain asymptomatic throughout life, reports of acute inflammation, perforation, haemorrhage, intussusception, intestinal obstruction, vesicodiverticular fistulae and primary tumours are described. We present a rare diagnosis of diverticulotransverse colonic fistula and its management.